2011
DOI: 10.2310/jim.0b013e318238748e
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Intestinal Colonization with Extended-Spectrum Lactamase-Producing Enterobacteriaceae among Healthy Individuals

Abstract: BackgroundInfections caused by extended-spectrum β-lactamase (ESBL)–producing bacteria become an emerging problem in the community setting in many parts of the world.ObjectiveThe objective of the study was to determine fecal carriage of ESBL-producing organisms in a community setting.MethodsA total of 632 fecal specimens from healthy individuals were screened for ESBL using the agar screening test with MacConkey agar plates supplemented with 1 μg/mL of cefotaxime for selection of ESBL-producing strains and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…The prevalence of fecal ESBL-E found in a study conducted in Cairo by Abdul Rahman and El-Sherif in 2011, was similar to what we observed [14]. In that study, ESBL-E were detected phenotypically, without genotypic confirmation and the prevalence of CPE was not determined.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The prevalence of fecal ESBL-E found in a study conducted in Cairo by Abdul Rahman and El-Sherif in 2011, was similar to what we observed [14]. In that study, ESBL-E were detected phenotypically, without genotypic confirmation and the prevalence of CPE was not determined.…”
Section: Discussionsupporting
confidence: 87%
“…In Egypt, data on the prevalence of ESBL-E in the community remain scarce. A study performed in Cairo (urban population) reported high fecal carriage rate (63.3%) of ESBL-E among healthy individuals [14]. To the best of our knowledge, no previous research has been carried out to determine the fecal carriage rate of CPE in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the percentage of fecal ESBL-producing E. coli recovered is comparable to those reported from other parts of the world including Saudi Arabia [30] and Tunisia [14], but lower than those found in Egypt [18], Thailand [17], China [13], and Japan [31]. In our study, the majority of ESBL-producing E. coli was isolated from patients with community-acquired infections and not from hospitalized patients with diarrhea which suggests the ability of ESBL-producing isolates to spread in the community beyond the hospital environment and potentially exclude their limitation to nosocomial infections, thus helping to exacerbate public health concerns [5].…”
Section: Discussionsupporting
confidence: 74%
“…Notably, there was a considerable increase in the rate of ESBL fecal carriage (0.6%–6%) in healthy subjects in France over a 5-year period, and it was indicated that acquisition of ESBL E. coli was associated with common food sources and person-to-person transmission through oral–fecal route. 23 25 More recently, extremely higher rates of ESBL-producing commensal enterobacterial strains have been reported by Rahman et al (63.3%) from Egypt, 26 Sasaki et al (58.2%) from Thailand, 27 and Mathai et al (19%) from India. 28 These reports suggest the continuous evolution and dissemination of multiresistant enterobacterial commensals in the healthy guts.…”
Section: Discussionmentioning
confidence: 88%